Association Between Oral Health and Cardiovascular Risk In Patients With Hypertension: Retrospective Study - Dr. Manjunath Chekka, Dr. Siva Kumar Pendyala, Dr. Kameswari Kondreddy, Dr Sandhya Rathod Chavan, Dr. Ujjwala Makne Shelke, Dr. Fawaz Abdul Hamid Baig, Dr. K. Lakshmi Suvarna (Drugs and Cell Therapies in Hematology, 2021)
Aims Poor oral hygiene can provoke transient bacteremia and systemic inflammation. This study aims to investigate association of oral health and Cardiovascular risk in Hypertensive patients. Methods In this Study total 200 subjects were identified and were included in study from the general population. They had no previous history of any cardiovascular disease (history of atrial fibrillation, heart failure, or cardiac valvular diseases). For oral hygiene indicators, presence of periodontal disease, number of tooth brushings, any reasons of dental visit, professional dental cleaning, and number of missing teeth were investigated. Results During median follow-up of 5.5 years, 2.0% of cases of atrial fibrillation and 2.9% cases of heart failure occurred. In multivariate analysis after adjusting age, sex, socioeconomic status, regular exercise, alcohol consumption, body mass index, hypertension, diabetes, dyslipidemia, current smoking, renal disease, history of cancer, systolic blood pressure, blood and urine laboratory findings, frequent tooth brushing (3 times/day) was significantly associated with attenuated risk of atrial fibrillation (hazard ratio: 0.90, 95% confidence interval (0.83–0.98)) and heart failure (0.88, (0.82–0.94)). Professional dental cleaning was negatively (0.93, (0.88–0.99)), while number of missing teeth was positively (1.32, (1.11–1.56)) associated with risk of heart failure. conclusion Improved oral hygiene care was associated with decreased risk of Cardiovascular disease in hypertensive patients. Therefore healthier oral hygiene by frequent tooth brushing and professional dental cleaning may reduce risk of Cardiovascular disorder.